Passage through phenophases by milkvetches introduced into the environments of the Kulunda Steppe - T. V. Kornievskaya (Труды по прикладной ботанике, генетике и селекции)
Background. Recently, more and more attention has been paid to the study of plant phenology in the context of the global climate change. By now, the question of how climate factors affect the phenophases of plants has not yet been fully investigated. Accurate forecasts for biological responses of plant species to climate change require profound understanding of the impact produced by meteorological factors on plant phenology.Materials and methods. The research was targeted at Astragalus L. spp. introduced into the dry steppe areas of the Kulunda Plain. Meteorological indicators were selected for agrometeorological description of the plant introduction site to assess its hydrothermal conditions. The Pearson correlation coefficient was used to identify the level of correlations between the studied parameters.Results. High air temperature shortened the growing season of Astragalus cicer L., but lengthened its flowering and fruiting phases. An increase in relative air humidity shortened the flowering in A. cicer. Meteorological indicators did not significantly affect the duration of the phenophases in A. sulcatus L. For A. onobrychis L., an increase in the average relative humidity reduced the budding phase, while an increase in the average and maximum air temperature and an increase in the amount of precipitation increased the flowering period. A decrease in air temperature and average relative humidity, and an increase in the total precipitation lengthened the duration of fruiting in A. onobrychis. Increased average temperature and humidity reduced its fruiting phase.Conclusion. A. sulcatus is tolerant to the dry steppe environments. The phenophases of A. cicer and A. onobrychis are more responsive to changes in meteorological indicators. In A. onobrychis, the fruiting phase is susceptible to the combined impact of climate factors. The limiting factors for A. cicer are relative humidity, total precipitation and mean temperature during the growing season.